2018
DOI: 10.1002/2017jc013263
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Low Light Requirement for Algae Growth Underneath Sea Ice: A Case Study From Station Nord, NE Greenland

Abstract: Microalgae colonizing the underside of sea ice in spring are a key component of the Arctic foodweb as they drive early primary production and transport of carbon from the atmosphere to the ocean interior. Onset of the spring bloom of ice algae is typically limited by the availability of light, and the current consensus is that a few tens‐of‐centimeters of snow is enough to prevent sufficient solar radiation to reach underneath the sea ice. We challenge this consensus, and investigated the onset and the light r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 75 publications
12
73
1
Order By: Relevance
“…Our observations are in accordance with Obertegger, Obrador, and Flaim () who analysed under‐ice DO dynamics in an oligotrophic lake, and with Hanke et al. () who studied phytoplankton growth and photosynthesis under thick snow and sea‐ice in Greenland.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are in accordance with Obertegger, Obrador, and Flaim () who analysed under‐ice DO dynamics in an oligotrophic lake, and with Hanke et al. () who studied phytoplankton growth and photosynthesis under thick snow and sea‐ice in Greenland.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the ice algae in this study were able to grow at extremely low irradiance (0.2 µmol photons m −2 s −1 ). This result is comparable to a recent study in Northern Greenland, where ice algae were observed to begin to grow at a light intensity below 0.17 µmol photons m −2 s −1 (Hancke et al 2018).…”
Section: Biological Activity In First-year Sea Ice and Newly Formed Ssupporting
confidence: 89%
“…These very low algal biomass and productivity values for Young Sound can be attributed to light limitation, given the late-winter sampling date and the heavy snow cover of 70 cm at the FYI site compared to 17 cm at POLY I, as well as other features of the snow and ice. Light attenuation by snow in this study is higher than reported elsewhere (Hancke et al 2018), particularly at the POLY I site (Fig. 1c).…”
Section: Biological Activity In First-year Sea Ice and Newly Formed Scontrasting
confidence: 61%
“…Low-light conditions are recognized to sustain ice algal growth (Leu et al, 2015;Lacour et al, 2017;Hancke et al, 2018). Although contributions of ice algae to the annual primary production remain highly variable, depending on the season and the region (<1 to 60%; e.g., Loose et al, 2011;Dupont, 2012;Fernández-Méndez et al, 2015), they are a critical food source for the marine food web especially during the winter (Søreide et al, 2010).…”
Section: Research Articlementioning
confidence: 99%